Financial Repression and Inequality towards Economic Growth during the Pandemic in Indonesia - Prasetyowati, Riris Aishah; Meiria, Endah (Center for Risk Management & Sustainability and RSF Press, 2021)
Background – During the pandemic, the global economy was greatly affected, including Indonesia. Currently, Indonesian government expenditure is focused on overcoming the impact of the pandemic by implementing policies in various sectors that have a major impact on vulnerable communities. This causes widespread poverty, which is indicated by the occurrence of income inequality due to government policies through financial repression that possibly affects economic growth. Purpose – This study aims, first, to analyze the financial repression policies carried out by the Indonesian government during the pandemic (2019-2021 period) on Indonesia's economic growth as a developing country. The second objective is that the impact of financial repression carried out as a government policy will be studied more deeply on income inequality because most of the Indonesian population works in the informal sector. The third objective is to further analyze the relationship and impact of the two macroeconomic factors (financial repression and income inequality) simultaneously in the midst of a pandemic that affects economic growth in Indonesia. Design/methodology/approach – This study uses a quantitative and descriptive exploratory approach with secondary data. Data analysis used simultaneous equations with 2 Stage Least Square. Findings – The results of this study prove that income inequality and financial repression have no significant effect on the level of economic growth in Indonesia. However, in the opposite relationship, if the rate of economic growth is associated with the death rate of the population, which represents the condition of the COVID-19 pandemic, it shows a significant negative effect on the rate of economic growth and income inequality, as well as financial repression. Research limitations – This study is limited by the data period during the pandemic (late 2019 to July 2021) and the availability of data from the Badan Pusat Statistik (Central Bureau of Statistics) and the World Bank. Originality/value – The measurement of financial repression by the money supply and others, as a component of equation 1, and measurement of inequality using the Gini ratio or other poverty index as a component of equation 2. Both equations are linked to Indonesia's economic growth rate.